Integration of ISO 22000 (2018) and HAS 23000 through Management System Audit: Case Study in Corned Beef Producer - Elizabeth, Irma Rosiana; Suyatma, Nugraha Edhi; Yuliana, Nancy Dewy; Ranasasmita, Raafqi; Syaifullah, Syahnada Jaya (Indonesian Journal of Halal Research, 2021)
Integrated Management System (IMS) based audit can assist the internal and external auditor to conduct an audit effectively and efficiently while checking compliance of Food Safety Management System and Halal Assurance System in the food industry. Corned beef is a product categorized as critical both in terms of halal and food safety. Implementing a food safety management system and halal assurance in corned beef industries is a challenge for producers and external auditors from inspection agencies. Based on the requirements equality approach, an Integrated Management System can be developed, referring to ISO 22000 : 2018 and HAS 23000. This research aims to combine the requirements of ISO 22000 : 2018 and HAS 23000 to be used for audit activity, as well as formulating recommendations for the corned beef producers in both requirements based on a new version of ISO 22000 : 2018. According to the analysis of requirements equality on each requirement objective, there are 14 of 30 sub-clauses of ISO 22000 : 2018 that can be integrated with 9 HAS criteria. There are 2 HAS criteria that cannot be integrated with sub clauses of ISO 22000 : 2018, namely criteria number 4 material and 5 product. When the IMS clauses are used in audit to one of corned beef company, the percentage of compliance with the IMS requirements is 90.6% in PT XYZ. The nonconformities related to ISO 22000 : 2018 found on a new clause that has not existed in the previous version ISO 22000: 2005. This gap creates some recommendations for PT XYZ. However, IMS based audit makes the audit for halal and food safety compliance be more effective that can combine checking of food safety and halal in one audit. Furthermore, IMS based audit makes the audit be more time efficient, by reducing the mandays.